Ruthenium(II)‐ or Rhodium(III)‐Catalyzed Grignard‐Type Addition of Indolines and Indoles to Activated Carbonyl Compounds. Issue 17 (4th August 2016) - Jo, Hyeim; Park, Jihye; Choi, Miji; Sharma, Satyasheel; Jeon, Mijin; Mishra, Neeraj Kumar; Jeong, Taejoo; Han, Sangil; Kim, In Su
Abstract: The ruthenium(II)‐ or rhodium(III)‐catalyzed pyrimidinyl‐directed Grignard‐type C−H additions of N‐heterocycles with activated aldehydes and ketones are described. A cationic ruthenium catalyst and sodium acetate additive in dichloroethane as solvent were found to be optimal catalytic system for the construction of C‐7 alkylated indolines. In sharp contrast, a cationic rhodium complex allows the generation of C‐2 alkylated indoles and pyrroles as well as C‐1 alkylated carbazoles. The site‐selective C−H functionalization of these heterocyclic scaffolds could be an important asset towards the development of novel bioactive compounds. Abstract :